Implementasi Metode Pose to Pose pada Perancangan Animasi "Ali & Umar" - arfianto, farhan dzaffa; Hasan, Muhammad; Nugroho, Fresy; Karami, Ahmad Fahmi (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2025)
Animation, as a rapidly evolving art form, requires effective techniques to produce realistic and engaging movements. The pose-to-pose method, which focuses on creating key poses, is utilized in the design of the animation "Ali & Umar." This article explores the application of this method using Blender to enhance animation quality. Through this method, animators can better control each movement and add additional poses to increase dynamism. The pose-to-pose technique involves planning the animation by setting key poses at various stages of movement, allowing animators to achieve smooth and realistic motion and easily correct errors. The production process of this animation is divided into three main stages: preparation, creation, and refinement. In the preparation stage, the story and characters are designed with the help of artificial intelligence (AI) to facilitate initial visualization. The creation stage includes 3D modeling, texturing, rigging, and animating the characters and other visual elements, with the pose-to-pose method ensuring accurate character movements. Finally, the refinement stage involves editing and optimizing video quality and adding sound. The results of this study indicate that the pose-to-pose method is effective in producing educational 3D animations, aiming to convey an Islamic message about the dangers of shirk through an engaging medium. These findings open opportunities for the development of more innovative Islamic educational media in the future.